The Antinociceptive Effects of Midazolam on Three Different Types of Nociception in Mice - Shunsuke Chiba; Tomoki Nishiyama; Masanobu Yoshikawa; Yoshitsugu Yamada (Journal of Pharmacological Sciences, 2009)
Antinociceptive effects of systemically administered midazolam remain controversial. The present study was performed to investigate its antinociceptive effects on different types of nociception in mice. Four different doses of midazolam (1, 3, 10, and 30 mg/kg) were administered intraperitoneally (i.p.). Saline was used as a control. The hot plate test, tail pressure test, acetic acid writhing test, the running wheel test, and the balance beam test were performed following the drug administration. In the hot plate test and tail pressure test, i.p. midazolam produced significant antinociceptive effects with the 50% effective dose (ED50) of 3.46 mg/kg [confidence interval (CI), 1.99 – 6.01 mg/kg] and 3.52 mg/kg (CI, 2.77 – 4.47 mg/kg), respectively. In the acetic acid writhing test, i.p. midazolam also produced significant antinociceptive effects. In the running wheel test, no mice stopped running after saline or midazolam at 1, 3, or 10 mg/kg, but all mice stopped running 30 and 45 min after i.p. administration of midazolam at 30 mg/kg. In the balance beam test, 30 min after i.p. administration of saline or midazolam at 1, 3, and 10 mg/kg, all mice were able to stay on the beam for 90 s, none of them could with midazolam at 30 mg/kg. In conclusion, systemically administered midazolam had antinociceptive effects on acute thermal, acute mechanical, and acute inflammatory-induced nociception in mice. The antinociceptive potency of midazolam was the same for both acute thermal-induced nociception and mechanical-induced nociception. Keywords:: midazolam, antinociception, hot plate test, tail pressure test, acetic acid writhing test